2020
DOI: 10.3390/molecules25122907
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant, Anti-Inflammatory, and Neuroprotective Properties of the Synthetic Chalcone Derivative AN07

Abstract: Chalcones belong to a class of biologically active polyphenolic natural products. As a result of their simple chemical nature, they are easily synthesized and show a variety of promising biological activities. 2-Hydroxy-4′-methoxychalcone (AN07) is a synthetic chalcone derivate with potential anti-atherosclerosis effects. In this study, we demonstrated the novel antioxidant, anti-inflammatory, and neuroprotective effects of AN07. In RAW 264.7 macrophages, AN07 attenuated lipopolysaccharide (LPS)-induced elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 73 publications
0
28
0
Order By: Relevance
“…Previously it has been reported that 3-(3,5-di-tert-butyl-4-hydroxyphenyl)-5-(multi-substituted-4-hydroxyphenyl)-2-pyrazoli nes showed significant human LDL-antioxidant activities (Figure 1) [25]. These results demonstrated that bulky di-tert-butyl groups contribute to higher activity by creating It was demonstrated that synthetic chalcone derivative 2-hydroxy-4 -methoxychalcone (AN07) potentially has anti-atherosclerosis effects, as well as antioxidant, anti-inflammatory, and neuroprotective effects [11]. Some prenylchalcones are isolated from hops and beer and exhibit antioxidant effects, modulate metabolism of carcinogens by inhibition of distinct phase 1 metabolic enzymes and activation of phase 2 detoxifying enzymes, and display anti-inflammatory properties [12].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previously it has been reported that 3-(3,5-di-tert-butyl-4-hydroxyphenyl)-5-(multi-substituted-4-hydroxyphenyl)-2-pyrazoli nes showed significant human LDL-antioxidant activities (Figure 1) [25]. These results demonstrated that bulky di-tert-butyl groups contribute to higher activity by creating It was demonstrated that synthetic chalcone derivative 2-hydroxy-4 -methoxychalcone (AN07) potentially has anti-atherosclerosis effects, as well as antioxidant, anti-inflammatory, and neuroprotective effects [11]. Some prenylchalcones are isolated from hops and beer and exhibit antioxidant effects, modulate metabolism of carcinogens by inhibition of distinct phase 1 metabolic enzymes and activation of phase 2 detoxifying enzymes, and display anti-inflammatory properties [12].…”
Section: Introductionmentioning
confidence: 91%
“…[5][6][7][8][9][10]. It was demonstrated that synthetic chalcone derivative 2-hydroxy-4′-methoxychalcone (AN07) potentially has anti-atherosclerosis effects, as well as antioxidant, anti-inflammatory, and neuroprotective effects [11]. Some prenylchalcones are isolated from hops and beer and exhibit antioxidant effects, modulate metabolism of carcinogens by inhibition of distinct phase 1 metabolic enzymes and activation of phase 2 detoxifying enzymes, and display anti-inflammatory properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, both gp91-phox and SOD1 are related with the regulation of ROS level and oxidative stress. 47–49 Therefore, we further detected the expression levels of gp91-phox and SOD1 by Western blot. Figure 3A shows that the expression of gp91-phox was markedly increased in the Non-LSCs treated with IONPs, particularly in the Non-LSCs treated with IONPs plus Ara-C; the difference between the IONPs and IONPs plus Ara-C was statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of regulating gene expression, the LIMK1 gene could not only participate in regulating synaptic remodeling and cytoskeleton stability of hippocampal neurons but also affect neuron migration by regulating Cofilin [ 108 ]. The SNCA gene was responsible for encoding the α -syn protein, whose mutation, duplication, or triplet could lead to autosomal dominant PD [ 109 ].…”
Section: Flavonoidsmentioning
confidence: 99%